2018
DOI: 10.5812/jjnpp.65549
|View full text |Cite
|
Sign up to set email alerts
|

The Antidepressant Activity of Matricaria chamomilla and Melissa officinalis Ethanolic Extracts in Non-Reserpinized and Reserpinized Balb/C Mice

Abstract: Background: Matricaria chamomilla and Melissa officinalis have been used as antidepressants in traditional Iranian medicine. Objectives: The aim of this study was to determine the effectiveness of Matricaria chamomilla and Melissa officinalis extracts compared to the classic antidepressant drug, imipramine, in adult non-reserpinized and reserpinized mice through the forced swim test. Methods: In the current experimental study, 80 mice were divided into 10 groups. The first group received normal saline and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, sodium valproate decreases the brain glutamate level by inhibition of voltage-gated sodium channels, and preventing action potential firing (Zawab and Carmody, 2014). The present results are consistent with Kumar et al, (2016), who reported that pretreatment with sodium valproate led to substantial rise the GABA level in brain tissue.…”
Section: Phytochemical Screening Of Crude Flavonoids and Alkaloids Ex...supporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, sodium valproate decreases the brain glutamate level by inhibition of voltage-gated sodium channels, and preventing action potential firing (Zawab and Carmody, 2014). The present results are consistent with Kumar et al, (2016), who reported that pretreatment with sodium valproate led to substantial rise the GABA level in brain tissue.…”
Section: Phytochemical Screening Of Crude Flavonoids and Alkaloids Ex...supporting
confidence: 91%
“…It was well-known that PTZ triggers the production of free radicals. In addition, free radicals have an important role in the development and pathogenesis of convulsive seizures (Kumar et al, 2016). The development of convulsive seizures induces decreasing the antioxidant defense mechanism and increasing the generation of free radicals, which further induces the oxidative stress (Borowicz-Reutt and Czuczwar, 2020).…”
Section: Antioxidant Effects Of the Crude Flavonoids And Alkaloids Ex...mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, flavones can bind to GABA-A, which can have soothing and relaxing effects. Dietary flavonoids have multiple neuroprotective actions in central nervous pathophysiological conditions, including depression, and it was reported that naringenin can cause a potent antidepressant-like impact via central serotonergic and noradrenergic systems 19 . Radu et al investigated the effects of the M. chamomilla (chamomile) hydroalcoholic extract on anxiety and depression using a scopolamine rat model.…”
Section: Matricaria Recutita (Chamomile)mentioning
confidence: 99%
“…Matricaria chamomilla L. (MC), commonly known as German chamomile, is a traditional medicinal plant belonging to the Asteraceae family (7). Experimental studies have shown that the plant extracts possess a diverse range of medicinal properties such as anticonvulsant (8), antioxidant (9), antidepressant (10), anxiolytic (11), treatment of upper respiratory tract infection (12), and dermatitis (13), as it is rich in different bioactive compounds such as flavonoids (apigenin, quercetin, and luteolin), chamazulene, bisabolol, coumarins, and terpenoids (14).…”
Section: Introductionmentioning
confidence: 99%